THE APPLICATION OF OSTEOARTHRITIS GYMNASTICS AS AN EFFORT TO REDUCE PAIN LEVELS IN ELDERLY PEOPLE SUFFERING FROM OSTEOARTHRITIS AT POSYANDU LANSIA (INTEGRATED CARE FOR THE ELDERLY) IN THE WORKING AREA OF MOJOLABAN HEALTH CENTER, SUKOHARJO REGENCY - Riyani Wulandari Wulandari; Dewi Kartika Sari; Siti Fatmawai (P3M Universitas 'Aisyiyah Surakarta, 2022)
Introduction: Osteoarthritis has affected 7% of the worldâ€™s population, more than 500 million people worldwide, the number of people affected globally increased by 48% up to 2019. In 2019, osteoarthritis was the 15th highest cause of living with disability worldwide and was responsible for 2% of the global total. Non-pharmacological therapies, such as osteoarthritis gymnastics are used to reduce pain in knee osteoarthritis. Purpose: To find out the effect of osteoarthritis gymnastics on pain reduction in elderly who have knee osteoarthritis at Posyandu Lansia (integrated care for the elderly) in the working area of Mojolaban Health Center, Sukoharjo Regency. Method: The design in this study is a type of Quasi-Experimental research with a one group pretest-posttest design.Â Sampling techniques use purposive sampling techniques, with inclusion criteria by researchers. The sample size is 20 respondents. Results: The results of the bivariate test using the Wilcoxon test proved that there is a significant influence of osteoarthritis gymnastics on pain reduction in people with osteoarthritis with a value of p: 0.000 < 0.05. Conclusion: There is a significant influence of osteoarthritis exercise on pain reduction in people with osteoarthritis.